Towards a paradigm shift in the treatment of chronic chagas disease - Viotti, Rodolfo Jorge (2014)
Treatment for Chagas disease with currently available medications is recommended universally only for acute cases (all ages) and for children up to 14 years old. The World Health Organization, however, also recommends specific antiparasite treatment for all chronic-phase Trypanosoma cruzi-infected individuals, even though in current medical practice this remains controversial, and most physicians only prescribe palliative treatment for adult Chagas patients with dilated cardiomyopathy. The present opinion, prepared by members of the NHEPACHA network (Nuevas Herramientas para el Diagnóstico y la Evaluación del Paciente con Enfermedad de Chagas/New Tools for the Diagnosis and Evaluation of Chagas Disease Patients), reviews the paradigm shift based on clinical and immunological evidence and argues in favor of antiparasitic treatment for all chronic patients. We review the tools needed to monitor therapeutic efficacy and the potential criteria for evaluation of treatment efficacy beyond parasitological cure. Etiological treatment should now be mandatory for all adult chronic Chagas disease patients.